Noongar Identity and Community Media - Johnston, Michelle (School of Journalism and Communication, in association with the Centre for Critical and Cultural Studies, The University of Queensland, 2011)
The Noongar Aboriginal people are the traditional owners of the southwest of Western Australia, including the land on which the city of Perth is located. Their recent history has been dominated by brutal and racist government policies that have created a diverse and complex community working to rediscover and preserve Noongar culture. Community media can be an effective and empowering tool for preserving culture, shaping a contemporary Noongar identity and creating a dialogue between the Indigenous and non-Indigenous urban community of Perth. This article discusses issues of Noongar identity in Perth, and looks at how lessons from the past are shaping new Noongar media initiatives and the establishment of Noongar radio.